DESIGN OF HORIZONTAL SLOPE PIPE WITH DIFFERENT OPENING SIZES OF GEOTEXTILE - KHUZARINA, MARZUKI (Universiti Malaysia Sarawak, (UNIMAS), 2018)
This study evaluates the effectiveness of horizontal slope pipe wrapped with different apparent opening size (AOS) of double-layer geotextile installation in terms of increasing the water discharged and simultaneously reducing the sediment produced. Several studies have been accomplished so far by past researchers regarding the design of drain with various parameters including the use of geotextile as drain envelope in order to improve horizontal slope drainage system. Their studies result in having more water discharged with high sediment produced and vice versa. Four experiments were carried out in this study which are Experiment 1 (AOS Inner and Outer Geotextile = 0.26 mm), Experiment 2 (AOS Inner and Outer Geotextile = 0.19 mm), Experiment 3 (AOS Inner Geotextile = 0.19 mm, AOS Outer Geotextile = 0.26 mm) and Experiment 4 (AOS Inner Geotextile = 0.26 mm, AOS Outer Geotextile = 0.19 mm). It is distinguished by the used AOS of 0.19 mm or/and 0.26 mm in the double-layer system. The detailed of the doublelayer system are; (i) wrapped around the High Density Polyethylene (HDPE) pipe with a diameter of 25 mm indicate as inner geotextile (ii) wrapped around the quarry gravel which act as filter material indicate as outer geotextile. A caging was used to ease the installation of pipe and quarry gravel. It was placed at the bottom of a model box with a dimension of 25 cm width, 25 cm height and 56 cm length. The model box was filled with sand which was compacted by application of hand pressure. The rainfall event was introduced with the aid of a rainfall simulator. From the experiments performed, Experiment 1 has the highest percentage of water discharge and sediment which is due to the large AOS of 0.26 mm used on both inner and outer geotextile. The large AOS of 0.26 mm eases the flow of water but unable to retain the smaller particle of sand. Experiment 2 does not perform well in respect of having the lowest water discharged with high sediment produced. The design causes the water to trap in the sand which makes the sand quickly fully covered with water and takes time before it can pass through the geotextile to be discharged. Meanwhile, Experiment 3 hasthe lowest amount of sediment produced but the discharged flow is very inconsistent during the entire process which is believed to be due to AOS of 0.19 mm wrapped around the pipe causing difficulty for water movement into the pipe to be discharged. Experiment 4 is the most effective design because it has the second highest percentage of water discharged which is 19.95% against mass of water introduced and also second lowest amount of sediment produced with a value of 0.094 g. Therefore, it can be concluded that the application of double-layer system with the used of two different AOS of geotextile on the design has significantly increased the filtration capacity and facilitate the water discharged.